2007
DOI: 10.2320/matertrans.48.101
|View full text |Cite
|
Sign up to set email alerts
|

SAXS and XAFS Characterization of Precipitates in a High-Performance Cu–Ni–Si Alloy

Abstract: Analyses of small-angle X-ray scattering (SAXS) and X-ray absorption fine structure (XAFS) were performed for characterizing precipitates formed in a Cu-3.1 at %Ni-1.4 at%Si alloy, the strength and electrical conductivity of which were improved by aging. SAXS profiles and XAFS spectra of samples aged at 720 K for different periods of time after a solution treatment were measured. SAXS profiles of samples, which were aged after the solution treatment and subsequently cold rolled, were also measured to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…In addition, this method can also evaluate the characteristic features of atomic correlations. In fact, EXAFS was used for analyzing the local structure of nickel in Cu-Ni-Si alloys, where precipitation occurred by aging [7]. The results showed that as nickel dissolved in the copper matrix precipitated to form nickel silicide, the local structure of nickel changed by aging.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, this method can also evaluate the characteristic features of atomic correlations. In fact, EXAFS was used for analyzing the local structure of nickel in Cu-Ni-Si alloys, where precipitation occurred by aging [7]. The results showed that as nickel dissolved in the copper matrix precipitated to form nickel silicide, the local structure of nickel changed by aging.…”
Section: Introductionmentioning
confidence: 98%
“…However, the SAXS signal from copper alloys generally contains an intense background scattering from surface imperfections and concentration fluctuations [5,6], resulting in difficulty in analyzing SAXS profiles. In order to overcome this difficulty, the indirect Fourier transform (IFT) method has been applied to analyze SAXS profiles, so that the information of precipitates is successfully extracted from SAXS profiles that have intense background scattering [7]. With regard to the local structure of precipitates, extended X-ray absorption fine structure (EXAFS) analysis can be a powerful tool for characterizing the local structure around a specific solute element.…”
Section: Introductionmentioning
confidence: 99%
“…Takahashi et al [7,8] characterized the effects of ageing and Fe element addition on precipitates in a Cu-3.1Ni-1.4Si (at.%) alloy using small-angle X-ray scattering and extend X-ray absorption fine structure (EXAFS) techniques. They observed a change in the EXAFS signal at the Ni K-edge in the aged alloy samples.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the age-hardening precipitates in the alloys have been widely accepted as being δ-Ni 2 Si intermetallics with an orthorhombic structure [6][7][8][9][10][11][12][13][14][15][16][17], although other types of precipitates, such as β-Ni 3 Si, (Cu,Ni) 3 Si, and other metastable phases, might coexist [8,[12][13][14][15]. In their most recent study, Hu et al investigated the subsequent age-hardening of δ-Ni 2 Si precipitates (i.e., continuous precipitates (CPs)) that form during isothermal aging, and explained their behavior using classical theories of phase transformation in association with energy calculations [14]; the CPs in Cu-2.6 Ni-1.6 Si-0.5 Cr (in at.%) alloys did not exhibit any changes in their δ-Ni 2 Si crystal structure, but underwent changes in their morphology and other crystallographic features.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitating phase responsible for the age-hardening has been investigated by a number of researchers, especially regarding the early stages of aging [6][7][8][9][10][11][12][13][14][15]. To date, the age-hardening precipitates in the alloys have been widely accepted as being δ-Ni 2 Si intermetallics with an orthorhombic structure [6][7][8][9][10][11][12][13][14][15][16][17], although other types of precipitates, such as β-Ni 3 Si, (Cu,Ni) 3 Si, and other metastable phases, might coexist [8,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%